Kalero Oral Art in Dompu NTB in Linguistic and Literary Perspective: A Study of Structure and Meaning - Irwansyah, Irwansyah; Darni, Darni; Ahmadi, Anas; Subandiyah, Heny (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Kalero oral art is one form of cultural expression that has developed in the Dompu community, West Nusa Tenggara (NTB). This oral art contains literary, linguistic, and cultural values ​​that are the identity of the region. This article aims to analyze Kalero oral art from a linguistic and literary perspective, focusing on the structure and meaning contained therein. The approach used in this study is qualitative descriptive analysis, with data collection methods through observation and interviews with Kalero oral art practitioners in Dompu. The results of the study show that Kalero oral art has a distinctive structure, consisting of elements such as intonation, word choice, and rhythm in its delivery. In terms of meaning, this oral art not only contains moral and social messages, but also reflects the outlook on life of the Dompu community. This research is expected to contribute to the development of linguistic and literary studies in NTB and enrich understanding of the richness of oral culture in Indonesia.